Zonificación de las áreas propensas a incidentes por ataques de Crocodylus acutus en el Pacífico Central de Costa Rica utilizando un Sistema de Información Geográfico - Sandoval Murillo, Luis Fernando (2019)
In recent years, the incidence of attacks by crocodiles in Costa Rica has increased, which is associated with the development of human activities in areas considered as optimal in what I determine as the species’ potential habitat. Given the above, the present investigation proposes the identification of zones of interaction between the crocodile and the human being from the integration of physical-geographic variables through Geographic Information Systems (GIS). In this way, a theoretical compila-tion was carried out to identify the physical-geographical variables that make up the crocodile's habitat (slope, drainage network, flood areas and land use coverage), as well as the socio-environmental variables that influence the alteration and loss of habitat of the species (number of neighborhoods, population density, density of roads, and coverage of land use). Likewise, case records were integrated with crocodiles assisted by the fire department. It was possible to demonstrate that most of incidents occur in areas with high interaction (areas where a wide variety of anthropic activities are carried out within the potential habitat of this reptile.) In addition, the results ob-tained in the investigation constitute an important input in the decision-making at the policy and territorial order level in the Central Pacific Region, since tourism is one of the main economic activities that can be threatened by an attack by this species.